DESIGN OF WHEELCHAIR JIG AND FIXTURE IN WHEELCAIR ELECTRIC CAR - Subkhan Subkhan; Adhe Anggry (Manutech : Jurnal Teknologi Manufaktur, 2021)
In this research, the technology that will be developed relates to a wheelchair steering and alignment system that will be used in the framework of an electric car for wheelchair users (Wheelchair car) in daily accessibility. Wheelchair car and modification vehicle shown technology development to support their rights. Duration of access for existing modification vehicle needs more than 20 seconds since opening door through to turn the vehicle power on. Wheelchair Jig design with guide bar and fixture design with locator system locked by door closing achieve 8 seconds to access wheelchair get trough into cabin. This is 7 seconds faster than modification vehicle and 4 seconds longer than user with standard car.